Revitalizing MSMEs through Marketing Digitalization and Business Continuity Management (BCM) Toward MSMEs In Kota Medan, North Sumatera. - Ahmad Hermanto; Amilia Hasbullah (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
Micro Small and Medium Enterprises (MSMEs) experienced enormous economic pressure during the COVID-19 outbreak. These conditions have a direct effect on their business performance, especially on the value of sales, products and services produced, thereby impacting the sustainability of their business. Since Medan known as one of biggest city in Indonesia, where the existence of MSMEs have the significance role to generate income within the community, therefore this paper is intended to analyze how MSMEs are able to rise and can continue their business activities through efforts to implement the concept of Business Continuity Management (BCM) and digital marketing.